Artificial aeration of an overloaded constructed wetland improves hypoxia but does not ameliorate high nitrogen loads. (15th January 2023) - Allen, Danielle J.; Farrell, Mark; Huang, Jianyin; Plush, Simon; Mosley, Luke M.
Abstract: High organic loadings to constructed wetlands can result in water quality issues such as low dissolved oxygen and high ammonium concentrations, with artificial aeration a potential mitigation option. This study compared baseline (no aeration – NA), continuous aeration (CA), and intermittent aeration (IA) conditions to improve water quality in a tertiary treatment free water surface constructed wetland (FWS CW) with night time hypoxia/anoxia, and high nutrient concentrations. The response variables included dissolved oxygen (DO), total nitrogen (TN), ammonium nitrogen (NH4 + -N), nitrate nitrogen (NO3 − -N), total phosphorus (TP), phosphate (PO4 3– -P), and dissolved organic carbon (DOC). In situ aeration and monitoring was performed from April to June 2021 in a large, field-scale FWS CW, the Laratinga wetlands Mount Barker, South Australia. The results demonstrated that DO increased by an average 2.11 mg L −1 from NA to CA during the night and 1.26 mg L −1 and 1.84 mg L −1 from NA to IA during the night and day respectively when averaging over the basins. The C/N ratio was very low and there was no significant influence of DO on DOC concentrations. There was no significant difference in TN concentrations with the application of aeration aside from a decrease in the channel at night from NA to IA, and an increase in NH4 + -N resulted under IA compared with NA in Basin 1 and 2 during the day. This implies that the N loadings exceeded the wetland's ability to complete nutrient conversions at a rate that aligns with input rate. The concentrations of NO3 − -N increased at night under CA and IA treatments suggesting that some nitrification was promoted, or there was inhibition of dissimilatory nitrate reduction to ammonium. The concentrations of TP and PO4 3– -P significantly increased with the aeration compared with no aeration, however there was no difference between the aeration treatments. This suggested that increased sediment resuspension during aeration increased P in the water. There was no change in DOC with the application of aeration. Overall, the DO increased with aeration application and may be able to better support the wetland ecology; however, the Laratinga wetland is overloaded and the capacity of the wetland to effectively transform and remove nutrients is inhibited, even with the application of artificial aeration. Highlights: Dissolved oxygen increased with the application of continuous and intermittent aeration. There was no change in total nitrogen with aeration and ammonium levels remained high. There was a small increase in nitrate, and total and soluble phosphorus with aeration. Despite near-neutral pH values, unionised ammonia was calculated to be at toxic levels. Using aeration to manage systems with high nutrient loadings is challenging.